2007
DOI: 10.1177/0961203307081847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension and hyperhomocysteinemia on arterial thrombosis in primary antiphospholipid syndrome

Abstract: The aim of this study was to evaluate traditional risk factors for coronary artery disease (CAD), homocysteine, anti-oxidized low-density lipoprotein (anti-oxLDL), anti-lipoprotein lipase (anti-LPL) and endothelin-1 (ET-1) in patients with primary anti-phospholipid syndrome (APS), furthermore verify possible association among these variables and arterial thrombosis. Thirty-eight women with primary APS and 30 age-and-sex-matched controls were evaluated. Patients presented higher-LDL and triglycerides levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
2
26
2
1
Order By: Relevance
“…On the other hand, this is a modifiable condition, and treatment of hypertension may be the most important intervention to reduce arterial thrombosis in these patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this is a modifiable condition, and treatment of hypertension may be the most important intervention to reduce arterial thrombosis in these patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher mean triglyceride levels and significantly lower mean HDL levels were previously reported among PAPS patients in comparison with controls [30][31][32][33]. Some specific autoantibodies could influence lipoprotein levels and effects in these patients.…”
Section: Metabolic Syndrome In Primary Antiphospholipid Syndrome Patimentioning
confidence: 61%
“…Different authors have observed similar prevalences of hypertension among PAPS patients (22.4 and 26.3%) [3,31], not differing significantly from that in controls (20%). Nevertheless, among PAPS patients, hypertension was significantly more frequent in those with arterial thrombosis, with which it was independently associated [31].…”
Section: Metabolic Syndrome In Primary Antiphospholipid Syndrome Patimentioning
confidence: 64%
See 2 more Smart Citations